Factors associated with intent to quit tobacco use in Cyprus adolescents - Savvides, Elena Charis G.; Christophi, Costas A.; Paisi, Martha; Pampaka, Despina; Kinnunen, Taru H.; Connolly, Gregory N. (My University, 2014)
Objectives: To identify factors associated with adolescent smokers' desire to quit based on the 2006 Cyprus Global Youth Tobacco Survey. Methods: A cluster sample design was used to select a representative sample of students from all registered middle and high schools in Cyprus with >. 40 students in academic year 2005-2006. Multivariable logistic regression was used taking into account the weight associated with each of the respondents. Results: Out of the total sample with available information (N= 12,629), 1591 students were current smokers (weighted frequency = 14%) and were included in the analysis, with 734 (46.1%) of them reporting that they want to quit smoking. In both males and females, strong predictors of intention to quit smoking include past quit attempts and physical activity. Intention to quit is also associated with the belief that smoking is harmful to them and inversely associated with having peers who smoke, in boys, and the belief that smoking is harmful to others and perceiving smokers as less attractive, and inversely associated with pocket money, in girls. Conclusions: The present study has identified factors that appear to influence youth's intention to quit tobacco, which is of major importance in developing successful tobacco cessation programs targeting adolescents.
Keywords: Cigarette smoking; Cyprus; Global Youth Tobacco Survey; Intention to quit; Smoking cessation; Youth smoking